Detecting Optical Fiber Wavelength Shifts Induced by Sugar Solution Concentration Using Lagrange Interpolation - Ni'matut Tamimah; Aslam C. P. Siregar (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Optical fiber can be used as a sensor because changes in the surrounding medium affect light propagation. This study aims to detect changes in the wavelength of light in optical fiber caused by different sugar solution concentrations using Lagrange interpolation. This study uniquely integrates stripped-cladding optical fiber sensing with Lagrange interpolation to estimate unmeasured wavelength responses across varying sugar concentrations using a safe, environmentally friendly sugar solution. The method involved removing the cladding layer of the optical fiber and applying sugar solutions with concentrations from 44.444% to 54.545%. A 589-nm yellow LED was transmitted through the fiber and measured with a spectrometer. The results showed that increasing sugar concentration reduced the wavelength from 555.26 nm to 546.75 nm. Therefore, this method is effective for detecting changes in solution concentration. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality EducationSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production